ANALISIS POWER WHO DALAM PENANGANAN PANDEMI COVID-19 MELALUI PROGRAM CHSE KEMENPAREKRAF - Kusuma, Gamma; Resen, Putu Titah Kawitri; Suwecawangsa, Adi Putra (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 3 No 2 (2024): JURNAL DIKSHI, 2024)
T his study aims to analyze the power and function of international organizations through a study of the role of WHO in dealing with the COVID-19 pandemic in terms of the adoption of WHO health protocol standards by the Ministry of Tourism and Creative Economy of the Republic of Indonesia through the Clean, Health, Safety, Environment Sustainability (CHSE) program. This research is a qualitative descriptive research that uses data collection techniques through library research. This study uses a conceptual basis, the role and function of International Organizations and the Power of International Organization to frame the analysis of the topics raised. This study found that WHO as an international organization that plays roles and functions, namely information, rule making, rule application, and socialization and adoption of WHO health protocol standards by the Ministry of Tourism and Creative Economy of the Republic of Indonesia shows that WHO exercises power of IOs related to information and moral authority. This study looks at the Ministry of Tourism and Creative Economy's response to the WHO health protocol standard as evidence of the Power of International Organization or the strength possessed by WHO. Keywords : COVID-19, CHSE Certification, Kemenparekraf, World Health Organization .